A Review on Oil Spill Clean-up Using Bio-Sorbent Materials with Special Emphasis on Utilization of Kenaf Core Fibers - Jen Yen Tan; Siew Yan Low; Zhen Hong Ban; Parthiban Siwayanan (BioResources, 2021)
Thousands of oil spill incidents regrettably have occurred on a daily basis around the globe. Oil spills are a form of pollution that poses major catastrophic threats to marine ecosystems. Oil spill incidents commonly occur in the middle of the ocean, and the process to remove the oil becomes a great challenge. Absorbents, due to their good oil-absorbing characteristics, are becoming more popular nowadays as one of the effective oil spill clean-up methods. Among the many types of oil absorbents, plant fibers were also being studied to remove the oil spills from the sea surface. This paper reviews factors leading to oil spills, the detrimental effect of the oil spill on the environment, the oil spill removal methods, and the application of plant fibers as oil absorbent material. The paper also will highlight the latest development on the utilization of kenaf core fibers as oil-absorbent material and the use of oil absorbed kenaf core fibers as fuel briquette by taking advantage the high calorific value of the oil spill.